2017
DOI: 10.4103/0974-2727.214246
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of transfusion transmitted infections in healthy blood donors: A 5-year tertiary care hospital experience

Abstract: INTRODUCTION:Transfusion transmitted infections (TTIs) can cause threat to bloody safety as blood transfusion is an important mode of transmission of TTI to the recipient, hence, to prevent transmission of these diseases, screening tests on blood bags is an important step for blood safety.AIM:This study was undertaken with the aim of determining the seroprevalence of TTI in healthy blood donors in a tertiary care blood bank.MATERIALS AND METHODS:A retrospective study was carried out over a period of 5 years fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 21 publications
(29 reference statements)
3
24
2
2
Order By: Relevance
“…VDRL reactive donors were estimated at 0.66% in this study which is greater than calculated in other studies [2,6,7,9,12,13,14]. Transfusion transmitted syphilis is not a major hazard in modern blood transfusion therapy.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…VDRL reactive donors were estimated at 0.66% in this study which is greater than calculated in other studies [2,6,7,9,12,13,14]. Transfusion transmitted syphilis is not a major hazard in modern blood transfusion therapy.…”
Section: Discussioncontrasting
confidence: 51%
“…Every blood transfusion therefore carries a potential risk for transmissible diseases. HBV incidence is higher in our population (1.39%) as compared to other similar studies [2,6,7,13,14]. HBV positivity indicates a carrier state or an active infection.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…A study by Chandekar A et al, also showed that the number of blood donors progressively increased in 3 year study period, which coincides with the present study. 17 As per the study, seroprevalence of HBV is highest, 1.82 % (1003/54937) followed by HCV 0.31% (175/54937) in all the donors. The seropositivity for HIV is 0.23% (129/54937), for syphilis 0.04% (24/54937) and for malaria 0.01% (6/54937).…”
Section: Resultsmentioning
confidence: 54%
“…In a study by Osei E et al similar results were observed in which total of 576 blood donors were screened in 2014, out of which 520 (90%) were males and the 56 (10%)were females [13]. Another study in India by Chandekar S A et al out of 76,653 healthy donors, 70,363 (91.79%) were males and 6290 (8.21%) were females [14]. The less percentage of females in our study may be due to low socioeconomic status, child bearing age or may be social taboos.…”
Section: Discussionmentioning
confidence: 61%